Cosmopolitanism: Ideal of a Borderless World - Giri, Pradeep Kumar (DMC Research Journal, 2018)
All human beings belong to a single community based on a shared morality. Cosmopolitanism may demand a type of world government. It means much inclusive to moral, economic, and political relationships between nations or individuals of different nations. The concept of cosmopolitanism is that all human beings, regardless of their citizenship, religion, political affiliation and other forms of boundaries, belong to a single community. Cosmopolitanism as a theory considers the individual human being as the basic unit. The ideal of cosmopolitanism does not believe in any kind of border, rather it erases/transcends the borders created to narrow down and divide humans giving various names like nationality, culture, and religion.